Deterministic epidemic model for (SVCSyCAsyIR) pneumonia dynamics, with vaccination and temporal immunity - Dominic Otoo; Patrick Opoku; Sebil Charles; Asekiya Prince Kingsley (Infectious Disease Modelling, 2020)
Streptococcus pneumonia is one of the leading causes of mobility and mortality in children under 6 years and the elderly especially in developing countries in which Ghana, the study area is not an exception.In this paper, a model of the spread and control of bacterial pneumonia that include symptomatic carriers, asymptomatic carriers and vaccination is formulated and analyzed to determine the effect of the vaccination intervention.Analysis of the system show that the disease free equilibrium is stable if and only if the basic reproductive number R0<1. For R0≥1, the endemic equilibrium is globally stable and the disease persist. Numerical simulation on the system show that with effective vaccine intervention pneumonia infection can be eradicated in the long term.